Financing of Churches and Religious Associations in Poland Compared to Models Used in Selected Countries in Europe and the World - Joanna Cichorska; Barbara Cichorska; Daniel Tomczak (Finanse i Prawo Finansowe, 2024)
The purpose of the article. To review the regulations regarding the financing of churches and religious associations used in selected countries.